(untitled) (Baghdad Science Journal, 2022)
In present work, new tetra-dentate ligand, titled 3,5-bis ((E)-5-Bromo-2-hydroxy benzylidene amino) benzoic acid (H3L), was prepared via an acid-catalyzed condensation process. New four metallic ligand complexes with Co(II), Ni(II), Cu(II) and Zn(II) ions, were also prepared from the refluxing of equivalent moles. Ligand’s structure and its complexes; were confirmed by numerous characterization methods, including Ultraviolet-Visible, Infrared, Mass Spectrometer, 1H and 13C Nuclear Magnetic Resonance spectra, atomic absorption, magnetic moments, and molar conductivity measurements. The results of the spectroscopic analyzes proved that the prepared ligand acts as tetradentate bi-ionic ligand and it was bonded to the metal ions by two nitrogen atoms of the two azomethine groups and by two oxygen atoms of the two phenolic hydroxyl groups after losing their two protons. Octahedral structure proposed to all prepared complexes. The (anti-bacterial) and (anti-fungal) activities of these compound were screened against (E. coli, S. aureus, Klebsiella spp., S. epidermidis,), and (Candida albicans). The results indicated that these compounds have moderated inhibition behavior. The activity of the prepared compounds against Acetyl Choline Esterase Enzyme (AChE) have also studied and the obtained data indicated the presence of different inhibition behavior.